Experimentally monitoring of the rapid biomolecular hydrolysis reaction with optical weak measurement. (1st December 2022) - Zhao, Ruitong; Wang, Xin; Wang, Peng; Wu, Xingda; Fang, Xianglin; Zhang, Yanjiao; Li, Shaoxin
Abstract: The real-time measurement of optical activity is of great significance for studying the chemical reactions of chiral molecules. In this study, we have built a set of linear common path optical weak measurement chiral sensor system in frequency domain, and the optical sensitivity of the system feasibly reaches 1524 for activity. Using this system, we have realized the state measurement of the ultrafast alkaline hydrolysis reaction of gluconolactone under different concentrations of catalyst. This study shows that the optical weak measurement chiral sensor can well monitor and compare the degree of hydrolysis reaction, and partly reflect the approximate change of the optical rotation in the real-time process of hydrolysis. Optical weak measurement chiral sensing does not require separation and labeling molecules, and has great application potential for the production and development of chiral compounds, especially chiral drugs.